Relationship between job stress and functional dyspepsia in display manufacturing sector workers: a cross-sectional study - Younghyeon Nam; Soon-Chan Kwon; Yong-Jin Lee; Eun-Chul Jang; Seung-hwan Ahn (Annals of Occupational and Environmental Medicine, 2018)
Abstract Background Job stress has been reported as a risk factor of psychological changes, which have been shown to be related to gastrointestinal diseases and symptoms such as functional dyspepsia. However, few studies have assessed the relationship between job stress and functional dyspepsia. Therefore, we investigated the relationship between job stress and functional dyspepsia in South Korea. Methods This study was conducted between May 23 and July 6, 2016 and included 901 workers in the display manufacturing sector. Subjects completed self-reported questionnaires, regarding Korean Occupational Stress Scale (KOSS), functional dyspepsia, Insomnia Severity Index-K, and health-related behaviors and job characteristics. Subjects were divided into functional dyspepsia-positive and -negative groups based on the Rome III criteria. The KOSS high-risk group was defined as subjects with KOSS score above the 75 percentile of KOSS reference value. Multiple logistic regression analysis was performed to investigate the association between job stress and functional dyspepsia. Results In women, the risk of functional dyspepsia was significantly higher in the high-risk groups of the following KOSS subcategories in unadjusted model: job demand (OR 3.282, 95% CI 1.181–9.126), and occupational climate (OR 2.665, 95% CI 1.041–6.823). Even in adjusted model, the risk was significantly higher in the high-risk groups of the following KOSS subcategories: job demand (OR 3.123, 95% CI 1.036–9.416) and occupational climate (OR 3.304, 95% CI 1.198–9.115). In men, the risk of functional dyspepsia was not significant in all KOSS subcategories. Conclusions This study showed that job demand and occupational climates were associated with functional dyspepsia in female display manufacturing sector workers. Therefore, both clinical and mental health approaches should be used in the management of functional dyspepsia in women.